An Investigation of the Dominant Theoretical Assumption in Epistemic Analysis of Some Systems of Knowledge - Akpan, Etorobong (LPPM Universitas Jambi, 2023)
An investigation into the epistemic analysis of some systems of knowledge was carried out. The aim of the project was to delineate the dominant theoretical assumption that guides epistemic analysis in these subjects of study. To achieve the objective, the method of content analysis was adopted for the study. The analysis was able to demonstrate that the dominant theoretical assumption guiding epistemic programmes in the selected systems of knowledge is the presupposition of the validity of absolute objective standpoint, which berates the inputs of the cognitive subject to knowledge claims.